Inovasi Pembelajaran Pendidikan Agama Islam Berbasis IT - Silalahi, Fitriana; Pohan, Indrawani; Rayani, Siti (Integrasi: Jurnal Studi Islam dan Humaniora, 2024)
This research reviews various aspects of innovation in IT-based PAI learning, including the use of mobile applications, e-learning platforms, and interactive multimedia. This innovative approach aims to increase understanding of religious concepts, facilitate interaction between teachers and students, and expand the accessibility of learning materials. Qualitative research methods are used to analyze the impact of this innovation on learning effectiveness, student participation, and improving the quality of religious education. The findings show that the integration of IT in PAI learning not only increases student interest, but also helps strengthen religious and ethical values. However, challenges such as technology accessibility, teacher training, and content monitoring remain concerns. This research highlights the importance of collaboration between stakeholders, including governments, educational institutions, and the IT industry, to develop sustainable, innovative solutions. Thus, innovation in IT-based PAI learning can make a significant contribution to improving the quality of Islamic religious education in the current digital era.